The Tourism Industry Competitive Potential Management - Bakalo, Nadiya; Hunchenko, Mariya; Sushchenko, Olena; Boycheva, Hristina (International Journal of Engineering and Technology, 2018)
The tourist branch enterprises competitiveness aspects are considered in the article. Major strategic opportunities for the development industry as well as disadvantages are specified. The competitiveness indices of the countries, which are formed in the components and are consolidated into the subindex, are singled out. The changes in the positions of Ukraine and some countries of the world in the competitiveness index in the tourism sector are analyzed. The properties of competitive advantages are considered and divided into internal and external ones.Â Â